2022
DOI: 10.34172/ijhpm.2022.6335
|View full text |Cite
|
Sign up to set email alerts
|

Job Performance of Medical Graduates With Compulsory Services in Underserved Rural Areas in China: A Cohort Study

Abstract: Background: China started a national program in 2010 to train qualified general practitioners with compulsory services (CSP) in rural and remote areas. While the program has shown positive effects on staffing primary health care in rural areas, very little is known about how well they perform. This study aims to evaluate the job performance of medical graduates from this program and the influence of program design on job performance. Methods: A cohort study was conducted with graduates from CSP and non-CSP (NC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The average scores of the dimensions showed that dedication was the highest and task performance was the lowest. The highest score in the dimension of job dedication may be attributed to the fact that the medical staff in this study are younger, mostly with a bachelor's degree or above, and are in a critical period of striving, so they are more willing to try challenging jobs higher than their own level (Li et al, 2022 ). At the same time, the sense of accomplishment and responsibility brought by the profession of medical personnel may also motivate them to increase work engagement, resulting in better performance (Levin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…The average scores of the dimensions showed that dedication was the highest and task performance was the lowest. The highest score in the dimension of job dedication may be attributed to the fact that the medical staff in this study are younger, mostly with a bachelor's degree or above, and are in a critical period of striving, so they are more willing to try challenging jobs higher than their own level (Li et al, 2022 ). At the same time, the sense of accomplishment and responsibility brought by the profession of medical personnel may also motivate them to increase work engagement, resulting in better performance (Levin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…Normally, the natural and socioeconomic conditions are much more difficult for undeveloped regions compared with other regions. So using innovative ways to alleviate the gap between affluent and poor areas in terms of quality of care and health status is essential,41 like developing mobile health services17 or trying to start national programmes to train qualified general practitioners with compulsory services in rural and remote areas 42. Adopting a transfer payment system for cross-subsidies, with developed areas subsidising underdeveloped areas, could also be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…So using innovative ways to alleviate the gap between affluent and poor areas in terms of quality of care and health status is essential, 41 like developing mobile health services 17 or trying to start national programmes to train qualified general practitioners with compulsory services in rural and remote areas. 42 Adopting a transfer payment system for cross-subsidies, with developed areas subsidising underdeveloped areas, could also be helpful. Meanwhile, the Red River Delta and South East region should not be overlooked simply because of their relatively high levels of economic and healthcare development.…”
Section: Discussionmentioning
confidence: 99%
“…Students under this policy are required to complete five years of medical education, followed by three years of standardized training, and then serve for three years at township health clinics. As identified in existing research, a significant number of these medical students report low job satisfaction [ 20 , 21 ] with a pronounced intention to resign [ 22 ]. The principal reasons cited for this discontent are the low levels of pay, long working hours, scarce opportunities for further training, and limited prospects for career advancement.…”
Section: Discussionmentioning
confidence: 99%